O binômio mãe/filho na primeira gestação após os 35 anos - Cabral, Regina Aparecida (2015)
The aim of this study was to know the primiparous experience after 35 years old that was followed up in an ambulatory of high risk management in a city of the countryside of the state of São Paulo. It is about a descriptive, transversal study, with a qualitative approach, with the participation of 10 primiparous, during the period from January, 2013 to June, 2014. Data were collected through an instrument elaborated, comprising two parts: the part I with semi-structured data, concerning to the mother and the NB (newborn), collected from the medical history and complemented in the interview performed at home, and the part II with open questions directed to mothers on their opinion before the experience of having their children after being 35 years old. The results show that most of the participants was within the age between 35-37 years old, was married, had studied until high school and with an income from one to six minimal wages. Only one pregnancy was induced by drugs and all of them were of an only fetus. The main reasons to the forwarding to AGAR, were the hypertension and diabetes. All of them were subject to a caesarean. Only one mother presented complications (thromboembolism) and most of them were able to breastfeed with human breast milk exclusively. Among the complications of the NB, it can be highlight jaundice, hypoglycemia, dehydration and allergic to lactose. The reasons presented by having had their children older than 35 years old was the wait for financial stability, search for professionalization and the time taken to find the ideal partner. They report difficulty to get pregnant and to breastfeed. Most of them were supported by their partners and family, but they do not desire to have more children because they consider the maternity a difficult task. For them, pregnancy was seen as a positive experience, of achievement, that is worth to be faced. Generally, the study allowed to know a little about the reality of the primiparous older than 35 years old and their NBs, and strengthen the need of higher concern with the first gestation of women older than 35 years old, must these be considered as a result of socio-demographic changes and the progress of the medicine. It highlights yet, the importance of new studies in this context, so that it is possible to follow up both quantitatively and qualitatively late pregnancies, providing the professionals of health, managers, politicians and students, subsides to better attend and mitigate the risks to such clientele.